High strength cold rolled steel sheet with excellent comprehensive formability and bending properties for automotive applications
Patent Information
- Application Number
- JP2023561357
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-07
- Filing Date
- 2022-04-05
- Publication Date
- 2025-04-08
AI Technical Summary
Conventional high-strength steels lack the necessary formability and bending properties required for producing complex automotive components, particularly those with tensile strengths of 980 MPa, such as B-pillar hinges and roof rails, which are essential for lightweight automotive structures.
A high-strength steel sheet with a specific alloy composition and microstructure, including elements like C, Mn, Si, Cr, and controlled amounts of other alloying elements, is produced using a continuous annealing line to achieve a microstructure with retained austenite, bainitic ferrite, and tempered martensite, ensuring excellent formability and bending properties.
The steel sheet achieves tensile strengths of 980-1180 MPa with a yield ratio of 0.50-0.72 and bendability of 0.5-2.0, suitable for complex automotive parts, meeting the requirements for industrial production and improving fuel efficiency.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a high strength steel sheet suitable for automotive applications. In particular, the present invention relates to a cold rolled steel sheet having a tensile strength of at least 980 MPa and having excellent comprehensive formability and excellent bending properties. [Background technology]
[0002] For a variety of applications, increasing strength levels is a prerequisite for lightweight construction, particularly in the automotive industry, since a reduction in vehicle mass results in a reduction in fuel consumption.
[0003] Automotive body parts are often stamped from steel sheets to form thin complex structural members. However, such parts cannot be produced from conventional high strength steels because their formability is too low for complex structural parts. For this reason, multi-phase transformation induced plasticity steels (TRIP steels) have come into the spotlight in recent years, particularly for use in automotive body structural parts.
[0004] TRIP steels have a multiphase microstructure that includes a metastable retained austenite phase that has the ability to produce the TRIP effect. When the steel is deformed, the austenite transforms to martensite, resulting in superior work hardening. This hardening effect acts to resist necking within the material and delay fracture in sheet forming operations. The microstructure of TRIP steels can significantly modify its mechanical properties.
[0005] WO 2018 / 09090 A1 discloses high strength TBF steels having a high yield ratio (local formability) with excellent resistance to edge cracking and a high hole expansion ratio.
[0006] Although these steels exhibit some attractive properties, there is a need for 980 MPa steel sheets with an improved property profile in terms of overall formability and bending properties, particularly for the use of such materials in automotive B-pillar hinges, roof rails, door panels or similar parts. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2018 / 09090A1 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention is directed to a high strength (TBF) steel plate having a tensile strength of 980-1180 MPa and good overall formability and good bending properties. Furthermore, it should be possible to produce the steel plate on an industrial scale in a continuous annealing line (CAL). The present invention aims to provide a steel composition that can be processed into complex structural components, where both the yield ratio and the bendability, which affect the overall formability, are important. This is particularly suitable for automotive B-pillar hinges, roof rails, door panels or similar parts. [Means for solving the problem]
[0009] The invention is set forth in the claims.
[0010] The steel sheet has a composition consisting of the following alloying elements (wt%): C 0.08~0.14 Mn 2.5~3.0 Si 0.7~1.1 Cr 0.05~0.4 Optionally, Al≦0.2 Nb≦0.1 Mo≦0.1 V ≦0.1 Ti≦0.1 Ca ≦0.05 Cu≦0.1 Ni ≦0.2 B ≦0.005 The balance consists of iron and impurities. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a graph plotting bendability Ri / t against yield ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The importance of the individual elements and the interactions between them, as well as the limitations of the chemical composition of the claimed alloys, are briefly described below. All percentages for the chemical composition of the steel are given throughout this specification in weight percent (wt.%). The amount of hard phases is given in volume percent (vol.%). The upper and lower limits of the individual elements are freely combinable within the limits presented in the claims. The accuracy of the numerical calculations can be increased by one or two orders of magnitude for all values given in this application. Thus, for example, a value given as 0.1% can also be expressed as 0.10 or 0.100%.
[0013] C: 0.08-0.14% C is important to stabilize austenite and obtain sufficient carbon in the retained austenite phase. C is also important to obtain the desired strength level. Generally, an increase in tensile strength of about 100 MPa is expected per 0.1% C. If C is less than 0.08%, it is difficult to reach a tensile strength of 980 MPa. If C exceeds 0.14%, weldability is impaired. The upper limit may be 0.13 or 0.12%. The lower limit may be 0.09 or 0.10%. The preferred range is 0.09-0.12%.
[0014] Preferably, the carbon equivalent CE L(=C+Si / 50+Mn / 25+P / 2+Cr / 25) should be within the range of 0.20 to 0.30.
[0015] Mn: 2.5-3.0% Manganese is a solid solution strengthening element that stabilizes austenite by lowering the Ms temperature and prevents the formation of ferrite and pearlite during cooling. Furthermore, Mn lowers the Ac3 temperature, which is important for the stability of austenite. At a content below 2.5%, it may be difficult to obtain the desired amount of retained austenite, tensile strength of 980 MPa, and the austenitizing temperature may be too high for conventional industrial annealing lines. Furthermore, at lower contents, it may be difficult to avoid the formation of polygonal ferrite. On the other hand, if the amount of Mn is more than 3.0%, segregation problems may occur because Mn accumulates in the liquid phase and causes banding, resulting in possible deterioration of workability. Therefore, the upper limit may be 3.0, 2.9, 2.8 or 2.7%. The lower limit may be 2.5 or 2.6%.
[0016] Silicon: 0.7 to 1.1% Si acts as a solid solution strengthening element and is important for ensuring the strength of thin steel sheets. Si suppresses the precipitation of cementite and is essential for the stabilization of austenite. However, if the content is too high, too much silicon oxide may form on the surface of the strip, which may cause cladding on the rolls in the CAL and lead to surface defects on the subsequently produced steel sheets. Therefore, the upper limit is 1.1%, and may be limited to 1.05, 1.0 or 0.95%. The lower limit may be 0.75 or 0.80%. The preferred range may be 0.7-1.0%.
[0017] Cr: 0.05~0.4% Cr is effective in increasing the strength of steel plate. Cr forms ferrite and delays the formation of pearlite and bainite. C3 Temperature and M SThe temperature decreases only slightly with increasing Cr content. Cr results in an increase in the amount of stable retained austenite. The amount of Cr is limited to 0.4%. The upper limit may be 0.35, 0.30 or 0.25%. The lower limit may be 0.10 or 0.15%. The preferred range is 0.1-0.3%.
[0018] Al:≦0.2% Al promotes ferrite formation and is commonly used as a deoxidizer as well. The Ms temperature is increased with increasing Al content. A further drawback of Al is that it results in a drastic increase in the Ac3 temperature, thus making it more difficult to austenitize the steel in the CAL. For these reasons, the Al content is preferably limited to less than 0.2%, more preferably less than 0.1%, and most preferably less than 0.06%.
[0019] Nb:≦0.1% Nb is commonly used in low alloy steels to improve strength and toughness due to its effect on grain size. Nb increases the strength-elongation balance by refining the retained austenite phase and matrix microstructure due to precipitation of NbC. The steel may contain Nb in an amount of 0.1% or less. Intentional addition of Nb is unnecessary according to the present invention. Therefore, the upper limit may be limited to 0.03% or less. The upper limit may be further limited to 0.01 or 0.005%.
[0020] Mo≦0.1% Molybdenum can be added to improve strength. Molybdenum may further enhance the benefit of NbC precipitation by slowing down the carbide grain coarsening reaction rate. In accordance with the present invention, no intentional addition of Mo is required. Therefore, the upper limit may be limited to 0.03% or less. The upper limit may further be limited to 0.02% or 0.01%.
[0021] V:≦0.1% The function of V is similar to that of Nb in that it contributes to precipitation hardening and grain refinement. The steel may contain V in an amount of 0.1% or less. The upper limit may be limited to 0.09, 0.07, 0.05, 0.03 or 0.01%. According to the present invention, no intentional addition of V is required. Therefore, the upper limit may be limited to 0.01% or less.
[0022] Ti:≦0.1% Ti is generally used in low alloy steels to improve strength and toughness due to its effect on grain size by forming carbides, nitrides or carbonitrides. In particular, Ti is a strong nitride former and can be used to bind nitrogen in the steel. However, the effect tends to saturate above 0.1%. The upper limit may be limited to 0.09, 0.07, 0.05, 0.03 or 0.01%. In accordance with the present invention, no intentional addition of Ti is necessary. Therefore, the upper limit may be limited to 0.005% or less.
[0023] Ca≦0.05 Ca may be used to improve non-metallic inclusions. The upper limit is 0.05%, and may be set to 0.04, 0.03, or 0.01%. In accordance with the present invention, intentional addition of Ca is unnecessary. Therefore, the upper limit may be limited to 0.004% or less.
[0024] Cu:≦0.1% Cu is an undesirable impurity element and is limited to 0.1% or less by careful selection of the scrap used. The upper limit may be limited to 0.06% or less.
[0025] Ni:≦0.2% Ni is an undesirable impurity element and is limited to 0.2% or less by careful selection of the scrap used. The upper limit may be limited to 0.08% or less.
[0026] B:≦0.005% B is an undesirable impurity element and is limited to 0.005% or less by careful selection of the scrap used. B increases hardness, but may at the expense of reduced bendability, and is therefore undesirable in the steels suggested here. B also makes scrap recycling more difficult, and the addition of B may reduce workability as well. Therefore, according to the present invention, the intentional addition of B is undesirable. The upper limit may therefore be limited to 0.0006% or less.
[0027] Other impurity elements may be included in the steel in amounts normally present. However, it is preferred to limit the amounts of P, S, As, Zr and Sn to the following maximum arbitrary contents: P:≦0.02% S:≦0.005% As≦0.010% Zr≦0.005% Sn≦0.015%
[0028] Nitrogen content: It is also preferable to control N to ≦0.015%, preferably to a range of 0.003 to 0.008%, within which stable fixation of nitrogen can be achieved.
[0029] Oxygen and hydrogen further O:≦0.0003 H:≦0.0020 may be limited to.
[0030] The high strength TRIP assisted bainite ferrite (TBF) steel sheet of the present invention has a microstructure consisting mainly of retained austenite inclusions embedded in a matrix.
[0031] Microstructural percentages are expressed below in volume percent (vol.%).
[0032] The steel comprises a matrix of bainite ferrite (BF). The amount of bainite ferrite is therefore generally greater than or equal to 50%. The microstructure may also contain tempered martensite (TM) as well. The components BF and TM can be difficult to distinguish from one another. The total content of both components may therefore be limited to 70-90%. The amount is usually in the range of 75-85%.
[0033] Martensite may be present in the final microstructure, depending on its stability, since some austenite may transform to martensite during cooling at the end of the overaging step. Martensite may be present in an amount up to 15%, preferably up to 10%. This amount is usually in the range of 5-10%. These untempered martensite grains are often in close contact with the retained austenite grains, and therefore they are often referred to as martensite-austenite (MA) grains.
[0034] Retained austenite is a prerequisite for obtaining the desired TRIP effect. Therefore, the amount of retained austenite should be in the range of 2-20%, preferably 5-15%. The amount of retained austenite was measured using the saturation magnetization method as detailed in Proc. Int. Conf. on TRIP-aided high strength ferrous alloys (2002), Ghent, Belgium, p. 61-64.
[0035] Polygonal ferrite (PF) is not a desired microstructural component and is therefore limited to not more than 10%, preferably not more than 5%, not more than 3% or not more than 1%. Most preferably, the steel is free of PF.
[0036] The mechanical properties of the claimed steel are important and at least one of the following requirements must be met: Tensile strength (R m ) 980~1180MPa Yield strength (R p0.2) 580~750MPa Total elongation (A 50 ) ≧11% Yield ratio (R p0.2 / R m ) ≦0.72 Bendability (Ri / t) ≦2
[0037] Preferably, all of these requirements are met simultaneously.
[0038] Tensile strength (R m The upper limit of may be further limited to 1160, 1140, 1120, or 1100 MPa. The lower limit may be further limited to 990 or 1000 MPa.
[0039] Yield strength (R p0.2 The upper limit of ) may be further limited to 740, 730, 720, 710, 700, 690, 680, 670 or 660 MPa. The preferred interval is 580 to 700 MPa.
[0040] Yield ratio (R p0.2 / R m The upper limit of may be further limited to 0.71, 0.70, 0.69, 0.68, 0.67, 0.66 or 0.65. The lower limit may be 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57 or 0.58.
[0041] R m , R p0.2 value and total elongation (A 50 ) was derived according to Japanese Industrial Standard JIS Z 2241:2011, where samples were taken transversely across the strip.
[0042] The upper limit of the bendability Ri / t may be further limited to 1.9, 1.8, 1.7, 1.6 or 1.5. Preferably, Ri / t is less than or equal to 1.7, more preferably less than or equal to 1.5. The lower limit of Ri / t may be 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0.
[0043] The bendability is evaluated by the ratio of the critical bending radius (Ri), defined as the smallest bending radius without any cracks occurring, to the steel plate thickness (t). For this purpose, a 90° V-block is used to bend the steel plate according to JIS Z2248. The specimen size is 35 x 100 mm. The bending value Ri / t is obtained by dividing the critical bending radius in mm by the thickness in mm.
[0044] The mechanical properties of the steel sheet of the present invention can be adjusted to a large extent by the alloy composition and the microstructure, which can be adjusted by the heat treatment in the CAL, in particular by the isothermal treatment temperature in the overaging step.
[0045] The proposed steel can be produced by preparing converter melted conventional and secondary metallurgical steel slabs having the above mentioned composition. The slabs are hot rolled in the austenitic range into hot rolled billets. The slabs are preferably fully rolled in the austenitic range by reheating the slab to a temperature of 1000°C-1280°C, where the hot rolling finish temperature to obtain the rolled billets is 850°C or higher. The hot rolled billets are then coiled at a coiling temperature of 500-650°C. Optionally, the coiled billets are subjected to a descaling process such as pickling. The coiled billets are then batch annealed at a temperature in the range of 500-650°C, preferably 550-650°C, for 5-30 hours. The annealed billets are then cold rolled at a reduction of 35-90%, preferably around 40-60%. The cold rolled billet is further processed in a continuous annealing line (CAL).
[0046] The annealing cycle in the CAL includes a heating step to a temperature of 800-890°C, preferably 840-860°C, a soaking step for 80-180 seconds, preferably 100-140 seconds, a slow gas jet cooling step at a rate of 5-15°C / sec to a temperature of 700-750°C, a fast gas cooling step at a rate of 20-60°C / sec, preferably 30-50°C / sec to an overaging temperature of 405-460°C, a hold for 150-1000 seconds, and then a cooling step to room temperature. The overaging temperature may be upper limited to 450, 440, 430 or 420°C. The lower limit may be 405, 406, 407, 408, 409 or 410°C. The preferred range of the overaging temperature is 405-420°C. EXAMPLES
[0047] Steels I1-I3 and reference steels R1-R3 were produced by conventional and secondary metallurgy by converter melting. The compositions are shown in Table 1, further elements being present only as impurities, hereinafter the minimum levels of which are specified herein.
[0048] Table 1 shows the compositions of the steel sheets investigated.
[0049] [Table 1]
[0050] Slabs of steel alloys were produced in a continuous caster. The slabs were reheated and subjected to hot rolling to the thicknesses shown in Table 2. The hot rolling finish temperature was about 900°C and the coiling temperature was about 550°C. The hot rolled strips were pickled and batch annealed at about 620-625°C for 10 hours to reduce the tensile strength of the hot rolled strips and thus the cold rolling forces. The strips were then cold rolled in a 5-stand cold rolling mill to a final thickness of about 1.4 mm (I1, I3, R1, R2) or 1 mm (I2, R3) and finally subjected to continuous annealing.
[0051] The hot and cold rolling parameters are shown in Table 2. A batch anneal was performed between the hot and cold rolling steps for about 10 hours.
[0052] [Table 2]
[0053] The annealing cycle consisted of a heating step to a temperature of about 850°C, a soaking time of about 120 seconds, a slow gas jet cooling step at a rate of about 10°C / s to a temperature of about 720°C, a fast gas cooling step at a rate of about 40°C / s to an overaging temperature of above 405°C for the inventive examples and about 390-395°C for the non-inventive examples, an isothermal hold step at the overaging temperature, and a final cooling step to ambient temperature.
[0054] The details of the treatment in CAL are shown in Table 3. As can be seen from Table 4, different overaging temperatures affect the yield strength and bending properties of the steel.
[0055] [Table 3]
[0056] Materials produced in accordance with the present invention were found to have excellent mechanical properties as shown in Table 4.
[0057] All steels have tensile strengths in the range of 980-1180 MPa. Total elongation was greater than 11% for all steels.
[0058] Inventive examples I1-I3 have a yield strength less than 750 MPa. In detail, it can be pointed out that all inventive examples (embodiments) disclose a bendability (Ri / t) less than 2.0 in combination with a yield ratio less than 0.72. The highest Ri / t was 1.5 and the highest yield ratio was 0.64. Reference steels R1-R3 do not meet the requirements of yield ratio combined with yield strength and bendability.
[0059] Figure 1 is a diagram plotting the bendability Ri / t against the yield ratio. Examples I1-I3 are within the claim boundary of claim 1, marked "protected region", while reference examples R1-R3 are outside it.
[0060] [Table 4]
[0061] R m and R p0.2 The values are derived according to European standard EN 10002 Part 1, where the samples are taken in the longitudinal direction of the strip. Elongation (A 50 ) is derived in accordance with Japanese Industrial Standard JIS Z2241:2011 for samples taken transversely to the strip.
[0062] Ri / t was determined by V-bend test according to JIS Z2248. The produced strip samples (35×100 mm) were subjected to V-bend test to determine the critical bend radius (Ri). To investigate crack initiation, the samples were inspected both visually and under an optical microscope with a magnification of 25x. Ri / t was determined by dividing the critical bend radius (Ri) by the thickness (t) of the cold-rolled strip. Ri is the maximum radius at which the material does not show any cracks after three bend tests. [Industrial Applicability]
[0063] The material of the present invention is widely applicable to high-strength structural parts in automobiles. The high-strength steel plate is particularly suitable for producing parts with high requirements for overall formability and bendability. It is particularly suitable for automobile B-pillars, roof rails or door panels.
Claims
1. a) Composition (by weight) of the following elements: C 0.08~0.14 Mn 2.5-3.0 Si 0.7 to 1.1 Cr 0.05~0.4 Optionally, Al≦0.2 Nb≦0.1 Mo≦0.1 V≦0.1 Ti≦0.1 Ca≦0.05 Cu≦0.1 Ni≦0.2 B≦0.005 The balance, excluding impurities, is Fe, b) A multiphase microstructure (volume %) having: Retained austenite 2-20 Martensite ≦15 Bainite ferrite and tempered martensite 50-90 Polygonal ferrite ≦10 c) Tensile strength (R m ) 980~1180MPa Yield strength (R p0.2 ) 580~750MPa Yield ratio (R p0.2 / R m ) ≦0.72 d) the bendability value in a 90 ° V-bend test on a sample having dimensions of 35 × 100 mm, where Ri is the bending radius in mm and t is the thickness of the steel plate in mm, is Ri / t≦2.0; High strength cold rolled steel plate.
2. The high strength cold rolled steel sheet according to claim 1, wherein the microstructure satisfies at least one, preferably all, of the following requirements (volume %): Retained austenite 5-15 Martensite 5 to 10 Bainite ferrite and tempered martensite 70-90 Polygonal ferrite ≦5.
3. The high strength cold rolled steel sheet according to claim 1 or 2, wherein the composition (wt%) satisfies the following: C 0.09-0.12 Mn 2.5-2.9 Si 0.7 to 1.0 Cr 0.1 to 0.3 Al 0.005~0.1 Optionally, Nb≦0.1 Mo≦0.1 V≦0.1 Ti≦0.1 Ca≦0.05 Cu≦0.1 Ni≦0.2 B≦0.005 The balance, excluding impurities, is Fe.
4. The high strength cold rolled steel sheet according to claim 1 or 2, wherein the mechanical properties satisfy at least one of the following requirements: Tensile strength (R m ) 1000~1100MPa Yield strength (R p0.2 ) 580~700MPa Total elongation (A 50 ) ≧11% Yield ratio (R p0.2 / R m ) 0.50~0.70 Flexibility (Ri / t) ≦1.
7.
5. The high strength cold rolled steel sheet according to claim 1 or 2, wherein the mechanical properties satisfy the following requirements: Tensile strength (R m ) 1000~1100MPa Yield strength (R p0.2 ) 580~700MPa Total elongation (A 50 ) ≧11% Yield ratio (R p0.2 / R m ) 0.50~0.70 Flexibility (Ri / t) ≦1.
5.
6. The high strength cold rolled steel sheet according to claim 1 or 2, wherein the cold rolled steel sheet has a thickness of 0.9 to 1.6 mm.
7. 3. The high strength cold rolled steel sheet according to claim 1, wherein at least one of the elements selected from the group consisting of Nb, Mo, V, Ti and Ca is present as an impurity, and preferably, all of the elements selected from the group consisting of Nb, Mo, V, Ti and Ca are present as impurities.
8. A method for producing a cold rolled steel billet or sheet according to claim 1 or 2, comprising: a) providing a steel slab having a composition according to claim 1 or 2; b) hot rolling the austenitic slab into a hot rolled strip; c) coiling the hot-rolled strip at a coiling temperature in the range of 500 to 650°C; d) optionally subjecting the coiled steel billet to a descaling process; e) batch annealing at a temperature in the range of 500-650°C for 5-30 hours; f) cold rolling the annealed steel billet at a reduction of 35 to 90%; g) heating the strip to a temperature of 800°C to 890°C in a continuous annealing line and soaking for 80 to 180 seconds; h) slowly cooling the piece at a rate of 5-15°C / sec to a temperature of 700-750°C, then rapidly cooling at a rate of 20-60°C / sec to an overaging temperature of 405-460°C and holding for 150-1000 seconds; i) Cool to room temperature.
9. 3. An automotive structural component comprising the high strength cold rolled steel material according to claim 1 or 2.
10. 10. The automotive structural part of claim 9, wherein the structural part is a B-pillar hinge, a roof rail, or a door panel of an automotive vehicle.